Mortality attributable to smoking among HIV-1-infected individuals: a nationwide, population-based cohort study - Helleberg, Marie; Afzal, Shoaib; Kronborg, Gitte; Larsen, Carsten S; Pedersen, Gitte; Pedersen, Court; Gerstoft, Jan; Nordestgaard, Børge G; Obel, Niels (Clinical infectious diseases, 2013)
We assessed mortality attributable to smoking among patients with human immunodeficiency virus (HIV). We estimated mortality rates (MRs), mortality rate ratios (MRRs), life expectancies, life-years lost, and population-attributable risk of death associated with smoking and with HIV among current and nonsmoking individuals from a population-based, nationwide HIV cohort and a cohort of matched HIV-negative individuals. A total of 2921 HIV patients and 10 642 controls were followed for 14 281 and 45 122 person-years, respectively. All-cause and non-AIDS-related mortality was substantially increased among smoking compared to nonsmoking HIV patients (MRR, 4.4 [95% confidence interval CI, 3.0-6.7] and 5.3 [95% CI, 3.2-8.8], respectively). Excess MR per 1000 person-years among current vs nonsmokers was 17.6 (95% CI, 13.3-21.9) for HIV patients and 4.8 (95% CI, 3.2-6.4) for controls. A 35-year-old HIV patient had a median life expectancy of 62.6 years (95% CI, 59.9-64.6) for smokers and 78.4 years (95% CI, 70.8-84.0) for nonsmokers; the numbers of life-years lost in association with smoking and HIV were 12.3 (95% CI, 8.1-16.4) and 5.1 (95% CI, 1.6-8.5). The population-attributable risk of death associated with smoking was 61.5% among HIV patients and 34.2% among controls. In a setting where HIV care is well organized and antiretroviral therapy is free of charge, HIV-infected smokers lose more life-years to smoking than to HIV. The excess mortality of smokers is tripled and the population-attributable risk of death associated with smoking is doubled among HIV patients compared to the background population.